Death and Culture: Digging through the archives of Tamar to compare the widow scripts inscribed by the Nguni culture on the African widows - Thabede, Slindile (Stellenbosch Theological Journal, 2026)
In a multitude of African cultures, profound beliefs and customs revolve around death and mourning, highlighting the differing significance attached to the death of a husband versus that of a wife. Across many African societies, the passing of a husband holds great importance, marked by intricate rituals, communal solidarity, and adherence to cultural practices. Additionally, the mourning period for the husband may extend for up to one year or two, whilst for the wife, it typically lasts up to three months. These mourning practices mirror the esteemed role held by the deceased within their social and familial circles. Often, widows face barriers to expressing the injustices they endure within marital settings. Thus, this research aims to uncover the inherent oppression widows experience in African traditional families while also illustrating how the body serves as the embodiment of cultural narratives within such marital and bereavement frameworks. Utilising the biblical narrative of Tamar, this study will reexamine the challenges widows face within the African cultural context of marriage and death.